2018
DOI: 10.3389/fgene.2018.00281
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Identification of Novel Long Non-coding RNAs and Their Potential Associations With Milk Proteins in Chinese Holstein Cows

Abstract: Long non-coding RNAs (lncRNAs) have emerged as a novel class of regulatory molecules involved in various biological processes. However, their role in milk performance is unknown. Here, whole transcriptome RNA sequencing was used to generate the lncRNA transcriptome profiles in mammary tissue samples from 6 Chinese Holstein cows with 3 extremely high and 3 low milk protein percentage phenotypes. In this study, 6,450 lncRNA transcripts were identified through 5 stringent steps and filtration by coding potential.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 75 publications
(90 reference statements)
1
26
0
Order By: Relevance
“…The majority of the variants from the non-coding related set are 'non_coding_transcript_exon_variant' (SI Appendix, Table S1) which is 'a sequence variant that changes non-coding exon sequence in a non-coding transcript' according to VEP (28). This group of variants can be associated with long non-coding RNAs and they are found to contribute to complex traits in humans (51) and cattle (52). Variants annotated as coding related, of which the majority of variants are missense and synonymous (SI Appendix, Table S1), had relatively low ranking of genetic importance to complex traits (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the variants from the non-coding related set are 'non_coding_transcript_exon_variant' (SI Appendix, Table S1) which is 'a sequence variant that changes non-coding exon sequence in a non-coding transcript' according to VEP (28). This group of variants can be associated with long non-coding RNAs and they are found to contribute to complex traits in humans (51) and cattle (52). Variants annotated as coding related, of which the majority of variants are missense and synonymous (SI Appendix, Table S1), had relatively low ranking of genetic importance to complex traits (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the expression of relevant genes associated with cashmere fineness is under regulated by noncoding RNAs. Long noncoding RNAs (lncRNAs) are longer than 200 nucleotides and are transcribed from DNA, but they do not code for proteins ( Cai et al, 2018 ; Liu et al, 2013 ). However, lncRNAs can regulate the expression of protein-coding genes at various levels, including epigenetic regulation ( Du et al, 2020 ; Wei et al, 2020 ), transcriptional regulation ( Fei et al, 2020 ; Lauer et al, 2020 ; Yin et al, 2019 ) and posttranscriptional regulation ( Mangum et al, 2020 ; Zhang et al., 2020a ; Zhang et al., 2020b ), thereby influencing various biological processes, such as cell growth, cycle, development and gamete formation; epigenetics; and implantation ( Kumar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of the current experiment was that mammary gland tissue harvested at the three stages of lactation was not from the same goats, which might overshadow the specific effects associated with lactation. A similar experimental approach for tissue collection and analyses has been utilized in previous work with dairy cows (Li et al, 2016;Cai et al, 2018). However, unlike dairy cows with a large udder mass, repeated mammary biopsies in small ruminants is riskier and prone to inducing cessation of lactogenesis.…”
Section: Discussionmentioning
confidence: 99%